Diversity, justice and slum upgrading: An intersectional approach to urban development. (December 2022) - Rigon, Andrea
Abstract: Slum upgrading interventions often assume that all residents have similar aspirations and needs. However, these neighbourhoods rank among the most unequal settlements, and interventions can create winners and losers. Different dimensions of diversity have to be taken into consideration in planning such interventions to ensure a just outcome. Through the analysis of specific examples of slum upgrading processes in Nairobi, the paper identifies three interlinked aspects of diversity that need to be considered. These relate to Fraser's dimensions of social justice and to the pillars of the right to the city. We find that slum upgrading projects assume that all residents aspire to better housing and are willing to invest their savings and effort to achieve this. However, this is not a priority for everyone living in informal settlements. For many, the informal settlement is a relatively cheap housing option located close to good educational and economic opportunities, allowing parents to save for children's education. Interventions in informal settlements seldom consider the impact of market dynamics on different groups of residents. In informal settlements with some rental housing, improved infrastructures can lead to sudden increases in rent, displacing the most vulnerable residents of the settlement. Attempts to take diversity into account in participatory processes with local residents generally only recognise a limited number of dimensions of identity. They tend to divide people based on one dimension only, as if there were no others. However, people have multiple identities and some can be more salient than others when it comes to slum upgrading. This paper argues for an intersectional and relational approach, focusing on the relations between residents, and between different groups of residents.